2020
DOI: 10.1002/cbin.11437
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β boosts the functionality of human bone marrow‐derived mesenchymal stromal cells

Abstract: Transforming growth factor β1 (TGFβ1) is a negative regulator of hematopoiesis, and yet, it is frequently found at the active sites of hematopoiesis. Here, we show for the first time that bone marrow-derived mononuclear cells (BM MNCs) secrete TGFβ1 in response to erythropoietin (EPO). We further show that human bone marrow-derived mesenchymal stromal cells (BMSCs) briefly exposed to the conditioned medium of EPOprimed MNCs, or purified TGFβ1, gain significantly increased hematopoiesis-supportive ability. Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…3A). As seen in our previous experiments [4], the EPO-primed undep MNCs showed a dose-dependent increase in the TGFβ1 secretion up to 2 IU/ml of EPO, but this level remained steady even when the EPO concentration was raised to 5 IU/ml. Interestingly, the CM of unprimed (0 IU/ml) CD15-dep MNCs contained a much higher level of TGFβ1, as compared to its undep-control counterpart (Fig.…”
Section: Identi Cation Of Cell Type(s) Involved In Epo-mediated Tgfβ1 Secretion By Bm Mncssupporting
confidence: 81%
See 4 more Smart Citations
“…3A). As seen in our previous experiments [4], the EPO-primed undep MNCs showed a dose-dependent increase in the TGFβ1 secretion up to 2 IU/ml of EPO, but this level remained steady even when the EPO concentration was raised to 5 IU/ml. Interestingly, the CM of unprimed (0 IU/ml) CD15-dep MNCs contained a much higher level of TGFβ1, as compared to its undep-control counterpart (Fig.…”
Section: Identi Cation Of Cell Type(s) Involved In Epo-mediated Tgfβ1 Secretion By Bm Mncssupporting
confidence: 81%
“…EPO functions by binding to and activating its cognate receptor, EPO-R, though non-EPO-Rmediated actions have also been reported [21]. We have recently demonstrated that BM MNCs secrete copious amounts of TGFβ1 when primed with EPO [4]. A small amount of EPO is constitutively present in the circulation (5 pM; ∼20 mU/mL; 100 pg/mL), and its level increases in response to hypoxia [22], hence it is logical to assume that a natural in-built mechanism must be operative in vivo to control excessive production of TGFβ1 in response to elevated levels of EPO.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations